TO COMPARE THE EFFICACY AND SAFETY OF RAMIPRIL VERSUS LOSARTAN IN POST-MYOCARDIAL INFARCTION PATIENTS - NEENA KATOCH; DINESH KUMAR BADYAL; RAJNEESH K CALTON; NIKHIL KUMAR; GAURAV GULREZ (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Renin–angiotensin–aldosterone system (RAAS) plays an important role in regulating post-myocardial infarction (post-MI) events. Ramipril and losartan act mainly by inhibiting RAAS. This study was designed to compare the efficacy and safety of ramipril against losartan in post-MI patients. Methods: A total of 100 enrolled patients were divided into two groups A and B of 50 each by computer-generated random numbers. Group A (n=50) patients were given ramipril 1.25–2.5 mg once a day and Group B (n=50) patients were given losartan 25–50 mg once a day. The patients were followed after 0, 1, and 3 months and at 6 months (optional). Efficacy was compared based on the left ventricular ejection fraction (LVEF%) and New York Heart Association class improvement. Safety was compared by considering ADRs, mortality, and biochemical test profile. Data were analyzed using unpaired t-test and Chi-square test. p<0.05 was considered to be statistically significant. Results: The mean LVEF% at 0 month for Group A was 40.6 ± 4.48 and for Group B was 39.6 ± 4.02 (p=0.212). The mean LVEF% at 6 months for Group A was 45.12 ± 4.6 and for Group B was 43.57 ± 4.03 (p=0.11). The most common side effects were headache in Group A and hypotension in Group B. Conclusion: Both ramipril and losartan are equally efficacious; however, losartan has a better safety profile than ramipril.